Local Actions to Foster Climate Change Adaptation through Sago Palm Development Initiatives: Examining the Case of South Sulawesi, Indonesia - Trisia, Marlisa Ayu; Metaragakusuma, Andi Patiware; Osozawa, Katsuya; Bai, Hu (European Journal of Sustainable Development, 2016)
Indonesia has a great potential supply from its local resources, namely sago palm. It could be an alternative crop because its production is not significantly influenced by climate. This paper interrogates local actions in South Sulawesi Province in promoting sago palm. An Analytic Hierarchy Process (AHP), in-depth interview and observation were used for this study. The findings show that sago palm still plays an important role in providing income and food for the local community. However, a drastic change happened due to the expansion of other profitable crops during late 1990s-2000s. Sago production has also decreased significantly by 86.9% from 2006 to 2013. Several local actions have been done to revive sago palm, however, these actions were not sustainable due to heavily independent action without support from local government. Now, small initiatives with the local government are being implemented. The local government is endorsing sago palm into Regional Medium-Term Development Plan (RPJMD) 2016-2020 as an alternative crop to adapt to climate change. They are also designing local regulation (PERDA) regarding the protection of sago palm. What is noteworthy is the strong commitment from the government and engaging stakeholders with rural communities wherein these became a key foundation for co-existence of sago palm for a more comprehensive view on sustainable development. Keywords: Climate change adaptation, local action, policy, sago palm, sustainable development